Exposing agents as web services: a case study using JADE and SPADE - Donâncio, Henrique; Casals, Arthur; Brandão, Anarosa A. F. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2019: Anais do XIII Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2019)
Agents are autonomous software components that can be combined into multiagent systems (MAS). They possess capabilities related to distributed systems. For this reason, agents have been studied along with web services and Web technologies in Service-Oriented Architectures (SOA). With the advent of new Web-related paradigms, the need of reviewing existing work in this area arises. In this paper we briefly review some of the existing work relating agents and web services. For this purpose, we perform a comparison between two existing multiagent platforms (JADE and SPADE) considering their ability to support agents as web services. This comparison is done using an existing implementation of a simple MAS in JADE and its re-implementation in SPADE.